2020
DOI: 10.1016/j.mehy.2020.109860
|View full text |Cite
|
Sign up to set email alerts
|

Iodine, a preventive and curative agent in the COVID-19 pandemic?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
3
Order By: Relevance
“…However, in vitro studies showed increased cytokine synthesis in leukocytes treated with NaI or Lugol solution (iodine plus KI), and an epidemiological study showed a decreased immune response in iodine-deficient schoolchildren, despite normal thyroid hormone levels [74] . Interestingly, in Japan, a country known for its high iodine intake by the general population, relatively low mortality from COVID-19 has been observed despite having the eldest population in the world and having adopted relatively moderate lockdown measures [75] . However, both iodine deficiency and excess iodine are associated with an increased risk of thyroid disorders, and excessive iodine intake can precipitate hyper- or hypothyroidism and thyroid autoimmunity in some individuals [76] .…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies showed increased cytokine synthesis in leukocytes treated with NaI or Lugol solution (iodine plus KI), and an epidemiological study showed a decreased immune response in iodine-deficient schoolchildren, despite normal thyroid hormone levels [74] . Interestingly, in Japan, a country known for its high iodine intake by the general population, relatively low mortality from COVID-19 has been observed despite having the eldest population in the world and having adopted relatively moderate lockdown measures [75] . However, both iodine deficiency and excess iodine are associated with an increased risk of thyroid disorders, and excessive iodine intake can precipitate hyper- or hypothyroidism and thyroid autoimmunity in some individuals [76] .…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that patients treated with oral formulations of iodine show better prognosis than the placebo hence establishing its role in treating the disease. It has also been hypothesized that less number of deaths seen in Japan despite boosting a large number of old age population is because of the role of iodine in supporting innate immunity against viral pathogens since Japanese are famous for taking higher amounts of iodine [ 21 ] Since different preparations have different concentration-dependent efficacy and side effects, this will provide us to a better idea of optimal dosage with better efficacy and limited toxicity. The efficacy of iodine complex which will be reported in our trial will be compared to those of other topical alternates used to stop viral growth in nasopharynx as published in literature to establish the superiority, if any, of the iodine-based preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Комісаренка та Інститутом гігієни праці НАМН України за підтримки Дитячого фонду ООН (ЮНІСЕФ), можна стверджувати, що дефіцит йоду є актуальним для всієї території України [5]. Наслідком ДЙ є зниження секреції тиреоїдних гормонів, що негативно впливає на імунну систему з розвитком соматичних та схильністю до частих респіраторних захворювань [6,7].…”
Section: вступunclassified